A Study of the Soil Characteristics and Estimated Crop Yields of the Upper Damodar 'Valley area (Soil Interpretation) - Sarkar, A.K.; Pandey, S.N. (Journal of Soil and Water Conservation, 2022)
The Upper Damodar Valley comprises an area of approximately 7000 sq. miles and is mostly situated in the Chotanagpur plateau region in the State of Bihar. It has been divided into 39 sub-catchments according to natural drainage system, by Dr. Gorrio, Ex-Forest Adviser to Soil Conservation Department, D.V.C.The area is characterised by mountaneous lands, rolling to undulating uplands and low lands. Erosion of varying nature is a great menace in the area which principally takes place due to geomorphologic condition of the land, slope, unfavourable soil characteristics say textural and stuctural make up of the soil, unscientfic use of the land and existing climatic condition. The DVC has constructed four multipurpose dams for controlling hydrological behaviour in the Upper Damodar Valley area thereby reducing the flood havoc in the lower valley region, i.e. in the West Bengal. But it is observed that the longivity of the dams is rapidly declining due to heavy siltation rate in the reservoirs from the catchment areas of the Damodar. Of the various land forms the upland including degraded part of forest is the most vulnerable part of erosion and need utmost care for soil conservation as well as cropping since existing cropping practice accelerates erosion.